0065 Using Simulation, Video Recording And Think-aloud To Explore Clinical Reasoning And Develop An Educational Pedagogy To Enhance Practice. (1st November 2014) - Thackray, Debbie
Abstract : Background: Clinical practice environments are complex, dynamic and often unpredictable. Increasing numbers of adverse patient outcomes have been reported internationally. Clinical reasoning is a vital skill for all health care professionals in order to avoid making the wrong decision for the patient; and essential in the development of expertise. However, there is little known about the best approach to teaching it, often being left to students to learn on clinical placement. Clinical reasoning is then dependent on the experience gained and is subject to great variation. Methodology: An observational study was conducted using video recording, think-aloud and debrief interviews to identify the actions, behaviour and thinking of eight experienced cardiorespiratory physiotherapists as they assessed and treated a simulated post-operative patient with respiratory complications in a simulated high dependency unit. A thematic analysis was conducted on the video data using a framework approach. Results: The sequential stages of the actions and behaviour of the physiotherapists and key components of their thinking were identified. These findings have been collated and combined with the underpinning learning theories of simulation to create a conceptual model, which can be used as a template for simulated learning. This can be integrated into the curriculum, mapped to the three levels of the undergraduate physiotherapy programme and extended to postgraduate training using established educational principles. The complexities of the scenarios are appropriately set for progression. Conclusion: Simulation was an effective medium to explore the clinical reasoning of eight experienced cardiorespiratory physiotherapists using a commonly encountered clinical scenario. The resulting simulation pedagogy may facilitate the development of clinical reasoning through deliberate rehearsal and practice; particularly aiding the development of cognitive processing skills. This research methodology and pedagogy may be transferable to other professions and may reduce adverse patient outcomes in the long-term. References: Bloom BS, Engelhart MD, Hill HH, Furst EJ, Krathwhol DR (1956). The Taxonomy and Illustrative Materials. IN: Bloom BS (ed.) Taxonomy of Educational Objectives, The Classification of Educational Goals, Handbook 1: Cognitive Domain. New York: David Mckay Company inc Dreyfus HL, Dreyfus SE, (1986). Mind over machine:The Power of Human Intuition and Expertise in the Era of the Computer. Oxford: Basil Blackwell Spencer L, Ritchie J, O'Connor W. (2003). Analysis: Practices, Principles and Processes. Ritchie & Lewis (eds) Qualitative Research Practice: A Guide for Social Science Students and Researchers. London: SAGE